2001
DOI: 10.1289/ehp.01109927
|View full text |Cite
|
Sign up to set email alerts
|

Specific accumulation and elimination kinetics of tris(4-chlorophenyl)methane, tris(4-chlorophenyl)methanol, and other persistent organochlorines in humans from Japan.

Abstract: We examined human adipose tissue, liver, and bile from humans in Japan to understand the contamination status, specific accumulation, and elimination of two newly identified environmental contaminants, tris(4-chlorophenyl)methane (TCPMe), tris(4-chlorophenyl)methanol (TCPMOH), and other persistent organochlorines such as polychlorinated biphenyls (PCBs), DDT and its metabolites (DDTs), hexachlorocyclohexane isomers (HCHs), hexachlorobenzene (HCB), and chlordane compounds (CHLs). TCPMe and TCPMOH concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Regarding excretion, the presence of POPs in human bile from autopsy samples with significant relationship to concentrations in blood, adipose fat and liver indicates biliary excretion of POPs [ 46 , 47 ]. NASH patients generally have increased levels of bile acids in both plasma and liver tissue [ 48 , 49 ] and an increase of serum bile acids in NASH as compared to less severe stages of NAFLD has been found in obese patients undergoing bariatric surgery [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding excretion, the presence of POPs in human bile from autopsy samples with significant relationship to concentrations in blood, adipose fat and liver indicates biliary excretion of POPs [ 46 , 47 ]. NASH patients generally have increased levels of bile acids in both plasma and liver tissue [ 48 , 49 ] and an increase of serum bile acids in NASH as compared to less severe stages of NAFLD has been found in obese patients undergoing bariatric surgery [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid-normalized concentrations of TCPMOH in sea otter livers (100 ng/g) were approximately ninefold greater than concentrations found in prey items (11 ng/g), suggesting biomagnification of this compound in the sea otter food chain. Earlier studies have also reported the biomagnification of TCPMOH in humans and marine wildlife [18,19]. Nevertheless, concentrations of TCPMOH in sea otter livers were lower than those found in livers of California sea lions from central California [20].…”
Section: Concentrations and Bioaccumulationmentioning
confidence: 99%
“…These concentrations of TCPM and TCPMOH were selected because they were less than half of the NOAEL concentrations for survival and deformities in zebrafish embryos (Navarrete et al, 2021;Yost et al, 2022). It is important to note that transplacental transfer of TCPMOH (3.3%-5.3%) and TCPM (0.55%-1.2%) has been confirmed in whales (Kajiwara, Kamikawa, et al, 2008) and maternal transfer of TCPMOH has been observed during lactation in seals (Kajiwara, Watanabe, et al, 2008) and humans (Minh et al, 2001). Therefore, direct transplacental perfusion of the fetus and oral exposure in infants is likely.…”
Section: Implications Future Directions and Conclusionmentioning
confidence: 96%